1993
DOI: 10.1016/0014-5793(93)80263-t
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA for cyclooxygenase‐1 and cyclooxygenase‐2 in human tissues

Abstract: The rate-limiting step in the formation of prostanoids is the conversion of arachidonic acid to prostaglandin H2 by cyclooxygenase, also known as prostaglandin G/H synthase/cyclooxygenase. Two forms of cyclooxygenase have been characterized: a ubiquitously expressed form (COX-1) and a recently described second form (COX-2) inducible by various factors including mitogens, hormones, serum and cytokines. Here we quantitate by the reverse transcriptase-polymerase chain reaction (RT-PCR) the expression of COX-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
289
1
12

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 541 publications
(315 citation statements)
references
References 28 publications
13
289
1
12
Order By: Relevance
“…An interesting question remains of how other cells of the kidney that are able to express COX are affected by high PGE # concentrations. Recent studies have noted that the kidney has low but measurable levels of COX-2 mRNA [30,31]. The fact that COX-2 mRNA has the AUUUA motif in its 3h-untranslated region [1], which is considered an mRNA-instability determinant, indicates the necessity of continuous stimulation for its expression.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting question remains of how other cells of the kidney that are able to express COX are affected by high PGE # concentrations. Recent studies have noted that the kidney has low but measurable levels of COX-2 mRNA [30,31]. The fact that COX-2 mRNA has the AUUUA motif in its 3h-untranslated region [1], which is considered an mRNA-instability determinant, indicates the necessity of continuous stimulation for its expression.…”
Section: Discussionmentioning
confidence: 99%
“…39 Although controversy exists on this point, COX-1 and -2 expression might be higher in the prostate in general regardless of disease processes. 40 Outcomes data up to 20 years ago indicated a cancer chemopreventive effect for anti-inflammatory medications. 41 Large epidemiologic studies have examined this effect in celecoxib in a variety of cancers.…”
Section: Celecoxibmentioning
confidence: 99%
“…[5][6][7] The expression and role of COX-2 in prostate cancer has been a topic of several reports over the decade. 8,9 There exists some controversy over the expression, detection and the putative role of COX-2 in prostate carcinogenesis and progression. While early studies reported high-level expression of COX-2 in prostate, findings from subsequent studies have been mixed.…”
mentioning
confidence: 99%